Toward an equitable true crime?: what Black and Missing and Murdered and Missing in Montana reveal about the media portrayal of missing black and indigenous women and girls - Slakoff, Danielle C. (True crime and women, 2025)
The Missing White Woman Syndrome refers to the over-representation of White missing women and girls in the news media. This syndrome is problematic because Black and Indigenous women and girls disappear at high rates within the United States but receive far less media coverage and police attention. While a growing body of literature exists regarding how White women and girl victims are over-represented in true crime media, to our knowledge, no researcher to date has examined television true crime instalments for how marginalised woman and girl victims are portrayed. Using inductive qualitative content analysis, this chapter examines two television true crime documentaries – HBO’s Black and Missing and Oxygen Network’s Murdered and Missing in Montana –for how the missingness of Black and Indigenous women and girls is portrayed within American true crime. Across the two documentaries, missingness is tied to three main elements: police failures; sex trafficking; and the vulnerability of Black and Indigenous women. Overall, these two documentaries break the true crime mould by examining societal and structural issues impacting Black and Indigenous women and girls.